Rent control from Ancient Rome to Paris Commune - Kholodilin, Konstantin (DIW Berlin, German Institute for Economic Research, 2024)
Urban areas confront a chronic shortage of housing, especially in the low-rent segment. This precarious situation is further exacerbated by major challenges, like the destruction of housing by wars and natural catastrophes, rapid increase of demand, or pandemics cutting incomes. In response, the authorities implement rent control that slows rent increases or even freezes rents. Rent control is ubiquitous, widely used at a large scale since World War I. However, its roots lie in a far more remote past, the first documented examples stemming from the Ancient Rome. Despite social and technological differences between then and now, the solutions found more than 2000 years ago bear a striking similarity with modern policies. Rapidly rising property prices, the COVID-19 pandemic, and the Ukrainian war pushed rent control back to the top of the political agenda. In this study, using logit model and survival analysis, I investigate the factors that led to introduction of rent control. I find that wars, foundation of universities, and presence of Jewish communities made the introduction of rent control more likely.
10419/300813
Keywords: Graue Literatur; rent control; housing policy; Antiquity; Middle Ages; logit model; Cox proportional hazards regression